Teaching Resilience : Enabling Factors for Effective Responses to COVID-19. - Baumber, Alex; Allen, Lucy; Key, Tyler; Kligyte, Giedre; Melvold, Jacqueline; Pratt, Susanne (Student Success v.12 n.3 p.14-25 https://doi.org/10.5204/ssj.1773, 2021)
The COVID-19 pandemic has disrupted higher education globally. Teaching staff have pivoted to online learning and employed a range of strategies to facilitate student success. Aside from offering a testing ground for innovative teaching strategies, the pandemic has also provided an opportunity to better understand the pre-existing conditions that enable higher education systems to be resilient - that is, to respond and adapt to disturbances in ways that retain the functions and structures essential for student success. This article presents a case study covering two transdisciplinary undergraduate courses at the University of Technology Sydney, Australia. The results highlight the importance of information flows, feedbacks, self-organisation, leadership, openness, trust, equity, diversity, reserves, social learning and nestedness. These results show that resilience frameworks developed by previous scholars are relevant to university teaching systems and offer guidance on which system features require protection and strengthening to enable effective responses to future disturbances. [Author abstract]